1993
DOI: 10.1165/ajrcmb/9.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase in Human and Rat Lung: Immunocytochemical and Histochemical Localization

Abstract: In this issue of TheJournal Clerch et al. (1) show that hyperoxia regulates lung manganese superoxide dismutase (MnSOD) through a nonreceptor-mediated pathway involving G proteins. These observations suggest a number of possibilities regarding the cell involved and signaling mechanism used. Regu lation of MnSOD expression is a critical element in the lung's response to multiple forms of oxidant stress. It is likely that the location of MnSOD in mitochondria imparts protection to electron transport chain compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
449
1
12

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(495 citation statements)
references
References 22 publications
33
449
1
12
Order By: Relevance
“…Consistent with the observation that corticosteroids inhibit the expression of inducible NOS (iNOS) in epithelial cells [14], it has been shown that inhaled steroids are effective not only in controlling airway inflammation, but also in lowering NO levels in exhaled air [13,19,20].…”
mentioning
confidence: 57%
“…Consistent with the observation that corticosteroids inhibit the expression of inducible NOS (iNOS) in epithelial cells [14], it has been shown that inhaled steroids are effective not only in controlling airway inflammation, but also in lowering NO levels in exhaled air [13,19,20].…”
mentioning
confidence: 57%
“…Cellular expression of bNOS and eNOS in different cell types of normal lung tissue and pulmonary cell cultures has been reported earlier (Kobzik et al, 1993;Shaul et al, 1994;Sherman et al, 1999). Cellular expression of iNOS in the lung parenchyma has so far only been observed after experimental endotoxin stimulation or in sections from patients suffering from inflammatory lung disease (Kobzik et al, 1993;Robbins et al, 1994;Tracey et al, 1994). However, recently all three NOS isoforms were shown by immunohistochemistry to be expressed in the developing lung, and all were assumed to contribute to NO generation functioning in normal lung physiology (Sherman et al, 1999;Xue et al, 1996).…”
mentioning
confidence: 95%
“…Three isoenzymes of NOS have been described Moncada and Higgs, 1993): the neuronal isoform bNOS (NOS-1) and an endothelial isoform eNOS (NOS-3) as constitutive isoenzymes, and a mitogeninducible isoform iNOS (NOS-2). Cellular expression of bNOS and eNOS in different cell types of normal lung tissue and pulmonary cell cultures has been reported earlier (Kobzik et al, 1993;Shaul et al, 1994;Sherman et al, 1999). Cellular expression of iNOS in the lung parenchyma has so far only been observed after experimental endotoxin stimulation or in sections from patients suffering from inflammatory lung disease (Kobzik et al, 1993;Robbins et al, 1994;Tracey et al, 1994).…”
mentioning
confidence: 95%
“…13,22 The diverse actions of NO could be explained by its capacity to chemically attack several molecules containing metals. Moreover, soluble mediators of immune responses can differentially modulate the inducible isoform of NOS.…”
Section: Nitric Oxide Productionmentioning
confidence: 99%